Exposure to ambient fine particulate matter and semen quality in Taiwan. Issue 2 (13th November 2017) - Lao, Xiang Qian; Zhang, Zilong; Lau, Alexis K H; Chan, Ta-Chien; Chuang, Yuan Chieh; Chan, Jimmy; Lin, Changqing; Guo, Cui; Jiang, Wun Kai; Tam, Tony; Hoek, Gerard; Kan, Haidong; et al.
Abstract : Objectives: Environmental exposure to chemicals has been considered a potential factor contributing to deteriorated semen quality. However, previous literature on exposure to air pollution and semen quality is inconsistent. We therefore investigated the health effects of short-term and long-term exposure to fine particulate matter (PM2.5 ) on semen quality in Taiwanese men from the general population. Methods: A cross-sectional study was conducted among 6475 male participants aged 15–49 years who participated in a standard medical examination programme in Taiwan between 2001 and 2014. Semen quality was assessed according to the WHO 1999 guidelines, including sperm concentration, total motility, progressive motility and morphology. Three-month and 2-year average PM2.5 concentrations were estimated at each participant's address using a spatiotemporal model based on satellite-derived aerosol optical depth data. Multivariable linear and logistic regressions were used to examine the associations between PM2.5 and semen quality. Results: A robust association was observed between exposure to PM2.5 and decreased normal morphology. Every increment of 5 µg/m 3 in 2-year average PM2.5 was significantly associated with a decrease of 1.29% in sperm normal morphology and a 26% increased risk of having the bottom 10% of sperm normal morphology, after adjusting for a wide range of potential confounders (p<0.001). On the other hand, an increment of 5 µg/m 3 in 2-year average PM2.5 was associated with an increase of 1.03×10 6 /mL in sperm concentration and a 10% decreased risk of being the bottom 10% of sperm concentration (both p<0.001). Similar results were found for 3-month PM2.5 . Conclusions: Exposure to ambient PM2.5 air pollution is associated with a lower level of sperm normal morphology and a higher level of sperm concentration.